Evaluation and comparison of vertical marginal fit of three different types of multiunit screw-retained framework fabricated for an implant-supported prosthesis - An in vitro study - Mahima Singh; Bhupender Kumar Yadav; Sumit Singh Phukela; Pankaj Ritwal; Abhishek Nagpal; Pulin Saluja (Wolters Kluwer Medknow Publications, 2022)
Aim: The present study aimed to evaluate on a comparative basis the vertical marginal fit between conventionally casted, direct metal laser sintered (DMLS), and milled computer-aided design/computer-aided manufacturing (CAD-CAM) one-piece metal framework supported by five implants using one-screw test and screw resistance test. Settings and Design: This is an in vitro study. Materials and Methods: Five implants were placed parallel to one other in a Styrofoam master model. A total of 30 implant-supported screw-retained superstructures were manufactured using three techniques, i.e., conventionally casted, milled, and sintered. To evaluate the vertical marginal discrepancy, screw resistance test, and one-screw test were used, and measurements were made using a stereomicroscope. Statistical Analysis Used: The data was analysed using two statistical tests, i.e., ANOVA and the post hoc Bonferroni test. Results: On evaluating the frameworks using one-screw test, the mean vertical misfit value at the terminal implant for the control group was 292.58 ± 15.46μm, for conventionally casted framework 398.41 ± 21.13 μm, for DMLS 343.44 ± 24.73 μm, and for CAD-CAM was 304.03 ± 14.23 μm, whereas the average misfit values at four implants on applying screw resistance test were 1268.65 ± 84.24 (control), 1774.88 ± 67.70 (casted), 1508.02 ± 62.19 (DMLS), and 1367.29 ± 81.87 (CAD-CAM). The average misfit values on two implants using screw resistance test were 635.02 ± 57.33 for the control group; for conventionally casted, it was 879.75 ± 35.93; for (DMLS) framework, it was 761.51 ± 32.85; and for milled CAD-CAM framework, it was 687.07 ± 42.17 μm. Conclusion: The mean vertical marginal discrepancy, when compared with control, was least in milled CAD-CAM frameworks, followed by sintered DMLS and conventionally casted frameworks. Hence, according to the present study, CAD/CAM technique is recommended to achieve maximum marginal fit in full mouth screw-retained implant-supported FDPs.